Mobile Based Real Time Property/Land For Sale Viewing Using Google Map And Communication Tool For Buyer And Client/Real Estate Agent - Leong, Benjamin E-Jenn (2021)
The global pandemic has taken a toll on businesses which caused them to transition from their traditional means of conducting business operations to a more digitalized manner through mobile applications, and the real estate industry is no exception. Real estate agents are gradually beginning to advertise their property listings on mobile applications more frequently, and property developers are releasing their own applications as well to provide an extension to their conventional booking systems. However, the property listing mobile applications that are currently available in today’s market is only limited to information searching and registration. Thus, this project aims to develop and implement a mobile based property market application that is capable of providing an enhanced virtual home viewing experience, allow appointment bookings to be made, able to reach out to real estate agents more conveniently and integrate an improved chat feature. Evolutionary prototyping was adopted as the preferred software development methodology for this project as it enables its requirements to be flexible and iteratively refined throughout the project’s implementation phase. In addition, a literature review was also conducted by analyzing existing applications that are currently available today to identify all the essential features that the developed application should contain, along with other areas which can be enhanced accordingly. Proper verification and validation of the implemented features and functionalities through unit, usability and user acceptance testing were also performed to ensure that all of them conform to the proposed requirements. All in all, it can be concluded that the project was a success as it managed to fulfil all of its objectives. Future enhancements can be made to implement more features and functionalities into the property listing application in order to be able to enhance its competitive advantage within the real estate industry.